Analisis Keberadaan Kampus UIN SMDD Bukittinggi Terhadap Perubahan Sosial Budaya dan Pendapatan Masyarakat Mengunakan Teori William Fielding Ogburn (W. F. Ogburn) - Sabri; Suhatman; Sari, Rika Novita; Febrianti, Eka; Asnah; Nasfi (Indra Institute Research & Publication, 2025)
Banuhampu is a small sub-district within Agam Regency. Based on observational data, before the establishment of the State Islamic Institute (UIN SMDD) Bukittinggi, the socio-cultural life of the community was still underdeveloped and unwilling to accept change, furthermore, their income was still low due to their livelihood as farmers, and the level of education at the tertiary level was still low. Many of their children who had graduated from high school/vocational school preferred to continue their education outside the area, such as Padang, and also preferred to work rather than continue their education. However, after the establishment of the UIN SMDD College, the level of education at the tertiary level has increased. This article aims to explain the impact of the presence of the UIN SMDD Bukittinggi campus on socio-cultural changes and income in Kubang Putiah. The method used is observational methods with qualitative research, as well as library studies in the form of literature studies. In addition to the increased level of education and changing the socio-cultural structure, the presence of the UIN SMDD campus also affects economic activities, namely local residents who live near the campus have new jobs as traders and build boarding houses and other economic activities so that they can increase their income. This research is limited to the community in Nagari Kubang Putih. It also uses the theoretical approach of William Fielding Ogburn (W.F. Ogburn).